Modeling the Optimal Portfolio: the Case of the Largest European Stock Exchanges - Florin Aliu; Artor Nuhiu; Besnik Krasniqi; Fisnik Aliu (Comparative Economic Research. Central and Eastern Europe, 2020)
Portfolio optimization is the main concern for portfolio managers. Financial securities are placed within the portfolio based on the investor's risk tolerance. The study measures the risk-reward relationship when the number of stocks in the portfolio increases. Six diverse portfolios have been created with a different number of stocks, such as portfolios with 47 stocks, 95 stocks, 142 stocks, 190 stocks, 239 stocks, and 287 stocks. Stock prices and trading volume were collected on a weekly basis from the six largest European stock exchanges (FTSE100, CAC40, FTSE MIB, IBEX35, DAX, and MDAX). Markowitz's (1952) diversification formula has been used to measure the risk level of the individual portfolios. The results of the study show that the diversification risk constantly decreases when we move from the portfolios with 47 stocks to the portfolios with 287 stocks. The weighted average returns increase on the portfolios with a higher number of stocks, which is contrary to the standard portfolio theories. The results of the study indicate managerial implications for financial investors that are focused exclusively on the largest European stock exchanges.
Keywords: G11; 330; Portfolio diversification; stock exchanges; correlation coefficient; volatility